Technology for biobanking African poultry breeds (primordial germ cell cryo-storage) - CGIAR Research Program on Livestock (2019)
The methodology has been well tested and is now available for uptake. The study has already proved that the technique would prevent the extinction of the local ecotype and allow multiplication when necessary.